Molecular diagnosis of autosomal dominant congenital cataract in two families from North India reveals a novel and a known variant in GJA8 and GJA3 - Vanita, Vanita; Goyal, Shiwali; Tibrewal, Shailja; Ganesh, Suma (Frontiers in Pediatrics, 2022)
Aims: To detect the underlying genetic defect in two autosomal dominant congenital cataract (ADCC) families. Methods: Detailed family history was collected, pedigrees drawn followed by slit-lamp examination and lens photography. Mutation screening was carried out in genes for crystallins and connexins by PCR and Sanger sequencing. Ethnically matched controls were tested for the identified variants. Different bioinformatics tools were used to assess the pathogenicity of the observed variants. Results: In an ADCC family with total cataract, a novel change (c.166A>G) (p.Thr56Ala) in GJA8 was identified. In another ADCC family having nuclear cataract, c.134G>C (p.Trp45Ser) in GJA3 has been detected. These variants co-segregated completely in patients in respective families and were neither observed in unaffected family members nor in ethnically matched 100 controls, thus excluding these as polymorphisms. Conclusions: Present study identifies a novel variant c.166A>G (p.Thr56Ala) in GJA8 in an ADCC family having total cataract and a previously known mutation c.134G>C (p.Trp45Ser) in GJA3 in another ADCC family. Thr56 in GJA8 seems to be a mutation hot-spot as previously an ADCC Mauritanian family harbored different substitution (p.Thr56Pro) at the same codon although for a different phenotype (nuclear cataract). Similarly, Trp45 in GJA3 appears as a mutation hot-spot as p.Trp45Ser has previously been reported for nuclear cataract in a Chinese ADCC family. p.Thr56 (GJA8) and p.Trp45 (GJA3) are in the extra-cellular loop 1 (EL1) in respective connexin proteins, which along with EL2 are essential for gap junctions’ formation, hemi-channels docking, and regulating voltage gating of the channels. Hence residues in these regions seem crucial for maintaining eye lens transparency.